Early assessment of the left ventricular function by epirubicin‐induced cardiotoxicity in postoperative breast cancer patients. Issue 11 (12th September 2017) - Luo, Runlan; Cui, Hongyan; Huang, Dongmei; Li, Guangsen
Abstract : Objective: Epirubicin (Epi) is a potent and effective drug for many malignant cancers with serious cardiotoxicity. Therefore, layer‐specific two‐dimensional speckle tracking echocardiography (2D‐STE) was used to evaluate the longitudinal and circumferential systolic function of the left ventricular for the early detection of cardiotoxicity in this retrospective work. Methods: Overall, 130 female patients with postoperative breast cancer who did not receive radiotherapy were classified into three groups: Group A (control group, n = 40) without any chemotherapy; Group B (n = 44) administered Epi at 180 ~ 240 mg/m 2 ; and Group C (n = 46) administered Epi at ≥360 mg/m 2 . Peak and global systolic longitudinal strains (GLS) in the total and endocardium, mid‐myocardium, and epicardium were measured and calculated from apical four‐chamber, apical two‐chamber, and left ventricular long‐axis views, respectively. Peak and global circumferential strains (GCS) in the total and endocardium, mid‐myocardium, and epicardium were measured and calculated from mitral annulus, papillary muscle, and apical levels of the short‐axis view, respectively. Results: The total GLS and GLS of the endocardium in every view were significantly reduced in group C compared with both groups A and B ( P  < .05), but there was no significant difference between groups A and B ( P  > .05). The GLS of the epicardium and mid‐myocardium in groups B and C were not significantly reduced ( P  > .05). There were no significant differences in the total GCS and layer‐specific GCS of endocardium, mid‐myocardium, and epicardium among the three groups ( P  > .05). Conclusions: Left ventricular longitudinal systolic dysfunction was detected. Moreover, an impaired endocardium was also detected in an early assessment by layer‐specific 2DSTE.